2005
DOI: 10.4103/0378-6323.13779
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two systems of classification of leprosy based on number of skin lesions and number of body areas involved - A clinicopathological concordance study

Abstract: Our findings suggest that patients with involvement of 2 or less body areas can be classified as PB leprosy and those with more than 2 body areas involved can be classified as MB leprosy for the purposes of therapy. The study of areas of involvement in leprosy patients not only provides additional patient information but also adds another parameter as a basis for the study of leprosy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…19 The commonest histological type in a study by Sharma et al and Rao et al was borderline tuberculoid leprosy and that by Pandya et al was indeterminate leprosy. 6,8,27 In our study, there was complete agreement between the clinical and histopathological diagnosis in 39.58% of the cases. Similar comparative studies by different authors showed complete agreement between clinical and histopathological diagnosis which ranged from 31.58% to 82%.…”
Section: Discussionmentioning
confidence: 67%
“…19 The commonest histological type in a study by Sharma et al and Rao et al was borderline tuberculoid leprosy and that by Pandya et al was indeterminate leprosy. 6,8,27 In our study, there was complete agreement between the clinical and histopathological diagnosis in 39.58% of the cases. Similar comparative studies by different authors showed complete agreement between clinical and histopathological diagnosis which ranged from 31.58% to 82%.…”
Section: Discussionmentioning
confidence: 67%
“…1 It affects primarily the peripheral nervous system and secondarily the skin. It can lead to deformities, sometimes irreversible, if not treated in time.…”
Section: Introductionmentioning
confidence: 99%
“…Unless promptly and adequately treated, it can result in deformity and disability. Three types of reactions recognized are classified as: (1) type 1 reaction (T1R), (2) type 2 reaction (T2R) or erythema nodosum leprosum (ENL), and (3) the Lucio phenomenon [28]. Type 1 LR (T1R) and type 2 LR (T2R) are the main causes of nerve damage and permanent disability.…”
Section: Leprosy Reactionsmentioning
confidence: 99%
“…They may have aches and pains in the extremities and loss of strength and/or sensory perception. Sign manifestations increased inflammation become erythematous swollen and may be tender looking like erysipelas, edema of extremities or face frequently accompanied by nerve involvement, rapid swelling with severe pain/tenderness (neuritis), and sometimes loss of nerve function [28].…”
Section: Type 1 Reactionmentioning
confidence: 99%
See 1 more Smart Citation